KORPUSGA ASOSLANUVCHI GRAMMATIK VA LEKSIKOGRAFIK TADQIQOTLAR («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Grammatical and lexicographic studies based on the corpus, the main tasks and linguistic issues facing the corpus linguistics are reflected in this article.
Keywords: corpus linguistics, lexicography, ideographic dictionary, ideographic tagging, thesaurus.